Penentuan Harga Jual Beli Tanah Dalam Pemungutan Bea Perolehan Hak Atas Tanah Dan Bangunan Di Kota Pekanbaru - Eka Yulianti Alwi (Faculty of Law, Andalas University, 2018)
The transfer of rights due to the sale and purchase of land and or building by an individual or entity may incur tax liability, usually called Tax on Right on Land and Building Granting or BPHTB as local tax imposed to a buyer. The basis for imposition of BPHTB is the Value Object Tax (NPOP) or the transaction price. If the NPOP is unknown or lower than the Taxable Sales Value (NJOP) of the tax on Land and Building (PBB) in the year of acquisition, the tax basis used is NJOP PBB. The BPHTB payment is based on the Self-Assessment System, in which the taxpayer is trusted to calculate his self. This article is aimed to determine of the sale and purchase price of land in the collection of BPHTB in Pekanbaru City. The research concludes that the determination of the sale and purchase price of land by Local Income Office or BAPENDA in collecting BPHTB is through adjustment of NJOP at Letter of Owed Tax Announce (SPPT) of PBB at the time of reporting SSPD BPHTB compared to the location of the object BPHTB by the Land Value Zone Appraiser( ZNT), or by conducting a field inspection of the BPHTB object of a sale and purchase agreement made by a Notary is referred to as a Deed of Sale and Purchase Agreement or PPJB fulfilling the conditions stipulated in Article 1320 of the Civil Code will be the basis in forming of AJB by PPAT and SSPD BPHTB form which has been filled completely the taxpayer along with the required payment proof for the verification of SSPD BPHTB form.